IMPACT OF GREEN HUMAN RESOURCE MANAGEMENT AND GREEN ENTREPRENEURIAL ORIENTATION ON SUSTAINABLE PERFORMANCE: CASE STUDY AT FOOD MANUFACTURING ENTERPRISES IN HO CHI MINH CITY - Nguyen Van It; Phan Xuan Cuong (HUIT Journal of Science, 2025)
This research focuses on how green human resource management and green entrepreneurial orientation affect sustainable performance through the regulatory function of environmental consciousness and the intermediate role of green supply chain management at Ho Chi Minh City businesses, with a particular emphasis on manufacturing firms. The research aims to shed more light on the connections between industrial firms and green practices and sustainable performance. Both qualitative and quantitative methodologies were employed in the investigation. The study's findings indicate that green human resource management positively affects green supply chain management and that green supply chain management acts as a bridge to transfer green human resource management effects to sustainable performance. Furthermore, the study's findings demonstrate that, in addition to environmental consciousness regulatory function in transferring green entrepreneurial orientation effects to sustainable performance, green entrepreneurial orientation has a favorable effect on sustainable performance. The study's findings have a significant and positive impact on the sustainable growth of manufacturing companies in Ho Chi Minh City and other growing economies.